2021
DOI: 10.1111/jam.15111
|View full text |Cite
|
Sign up to set email alerts
|

Endophyte roles in nutrient acquisition, root system architecture development and oxidative stress tolerance

Abstract: Plants associate with communities of microbes (bacteria and fungi) that play critical roles in plant development, nutrient acquisition, and oxidative stress tolerance. The major share of plant microbiota is endophytes which inhabit plant tissues and help them in various capacities. In this article, we have reviewed what is presently known with regard to how endophytic microbes interact with plants to modulate root development, branching, root hair formation, and their implications in overall plant development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 128 publications
(226 reference statements)
3
56
1
3
Order By: Relevance
“…Similar to our results, improvement in the root architecture by endophyte inoculation was also reported by other workers ( Maggini et al, 2019 ; Muthukumar and Sulaiman, 2021 ; Verma et al, 2021b ), specifically, improvement in root surface area ( Irizarry and White, 2017 ; Yakti et al, 2018 ), root branching ( Crush et al, 2004 ; Irizarry and White, 2017 ), root diameter ( Martinuz et al, 2015 ), number of tips ( Irizarry and White, 2017 ), etc. The improvement could be due to the production of a number of phytohormones, including IAA by the endophytes, that can modulate the endogenous levels of phytohormones in plants ( Verma et al, 2021a ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to our results, improvement in the root architecture by endophyte inoculation was also reported by other workers ( Maggini et al, 2019 ; Muthukumar and Sulaiman, 2021 ; Verma et al, 2021b ), specifically, improvement in root surface area ( Irizarry and White, 2017 ; Yakti et al, 2018 ), root branching ( Crush et al, 2004 ; Irizarry and White, 2017 ), root diameter ( Martinuz et al, 2015 ), number of tips ( Irizarry and White, 2017 ), etc. The improvement could be due to the production of a number of phytohormones, including IAA by the endophytes, that can modulate the endogenous levels of phytohormones in plants ( Verma et al, 2021a ).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the horizontal transmission of the endophytes from the surrounding to the system of the plant is crucial for the success of applied endophytic inoculants ( Verma et al, 2021b ). Magnificent studies have been done on the potential of endophytic inoculants ( Egamberdieva et al, 2016 ; Abdelshafy Mohamad et al, 2020 ); nevertheless, the adaptability on different crop hosts was least worked out.…”
Section: Introductionmentioning
confidence: 99%
“…The response of RSA to diverse environmental conditions and relevant regulation mechanisms are always attracting the attention of numerous excellent researchers to meet healthy food production when encountering with drought, flooding, salinity, and other adverse circumstances. Affected by intrinsic genetic and environmental factors ( Chen et al, 2016 ), such as root length, root branching, soil texture, nutrients, and water, RSA is also regulated by microorganisms like AMF ( Chen et al, 2017a ), endophyte ( Verma et al, 2021 ), and rhizobia ( Concha and Doerner, 2020 ). In our experiment, inoculation with AMF decreased the root morphogenesis overall as reflected in root biomass, TRL, TPA, TSA, and TV, which was not consistent with previous studies finding positive effects because of overall promotion of plant growth ( Chen et al, 2017a ; Xia et al, 2018 ; Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The profound effect of KAS1 and KAS4 treatment on root architecture development of seedlings may be because of their IAA activities. IAA is known to increase root architecture in plants and endophyte-mediated IAA effects on root development have been described in the past ( Maggini et al, 2019 ; Verma et al, 2021 ). A study of the interaction of Arabidopsis seedlings with Pseudomonas significantly improved the root structure, and further study suggested that bacterium-mediated auxin signaling is important for better development of root system architecture ( Zamioudis et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Successful colonization of SEB onto root surfaces and rhizospheres may help developing seedlings in nutrient acquisition in two ways; first, they may mineralize/solubilize nutrients in the rhizosphere, and these will be easily available to root hairs; secondly, within root parenchyma and root hair cells, nutrients may be extracted from bacteria oxidatively through the rhizophagy cycle ( Paungfoo-Lonhienne et al, 2010 ; White et al, 2018 ). It has been shown that the secretion of ethylene by bacteria, triggers release of superoxide by the root cell, and it is hypothesized that superoxide produced by root cells acts on bacteria in extraction of nutrients from cell walls and cytoplasm ( White et al, 2018 ; Chang et al, 2021 ; Verma et al, 2021 ). In this study, most of the isolates showed at least one extracellular enzyme production activity including cellulase, pectinase and amylase.…”
Section: Discussionmentioning
confidence: 99%